Study of some thermodynamic properties of poly (3,4-di-chloro benzyl methacrylate-co-ethyl methacrylate) using inverse gas chromatography - Kaya, I; Demirelli, K (Walter de Gruyter & Co, 2001)
Thermodynamic quantities were obtained for the interactions of poly (3,4-di-chloro benzyl methacrylate-co-ethyl methacrylate) poly (BMA-co- EMA) with alcohols, ketones, acetates, aromatics and alkanes by the inverse gas chromatography method at different temperatures. The specific retention volumes,V-g(o), the sorption enthalpy, DeltaH(1)(s), sorption free energy, DeltaG(1)(s), sorption entropy, DeltaS(1)(s), weight fraction activity coefficients of solute specimens at infinite dilution, Omega (infinity)(1), Flory-Huggins interaction parameters, chi (infinity)(12), between the polymers and solvents were determined. The partial molar free energy, DeltaG(1)(infinity), the partial molar heat of mixing,, at infinite dilution and the solubility parameters of the polymer, delta (2), were calculated at different temperatures. The glass transition temperatures, T-g, of poly (BMA-co-EMA) (18.82,%), poly (BMA-co-EMA) (30:70,%), poly (BMA-co-EMA) (40.60,%) and poly (BMA-co-EMA) (73:27,%) were found to be about 58 degreesC, 59 degreesC, 61 degreesC and 63 degreesC, respectively, as determined by differential scanning calorimetry (DSC). Alcohols, ketones, acetates, n-alkanes and aromatics were found to be nonsolvents for poly (BMA-co-EMA) at this temperatures. Also the solubility parameters for poly (BMA-co-EMA) (18:82,%) and poly (BMA-co-EMA) (40:60,%) at infinite dilution were also found by plotting the graph of [(delta (2)(1)/RT)-chi (infinity)(12)/V-1] versus solubility,parameters, delta (1), of these specimens.
Keywords: poly (3,4-di-chloro benzyl methacrylate-co-ethyl methacrylate; inverse gas chromatography; polymer-solvent interactions; solubility parameter